2013
DOI: 10.3138/ptc.2011-49
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and Responsiveness of Three Upper-Limb Tests in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Purpose: To determine (1) the relationship among three common upper-limb tests for patients with chronic obstructive pulmonary disease (COPD): unsupported upper limb exercise test (UULEX), 6-minute pegboard and ring test (6PBRT), and a muscle-strength test using a hand-held dynamometer; and (2) the responsiveness of these three tests to changes after pulmonary rehabilitation that included a resistance arm-training programme. Methods: The study was a secondary analysis of a randomized controlled trial (RCT). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
2
24
1
Order By: Relevance
“…We measured upper limb functional exercise capacity using the UULEX and found similar impairment as reported in people with COPD . We observed that 85% of patients with ILD reported arm fatigue as the primary reason for ending the UULEX.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We measured upper limb functional exercise capacity using the UULEX and found similar impairment as reported in people with COPD . We observed that 85% of patients with ILD reported arm fatigue as the primary reason for ending the UULEX.…”
Section: Discussionsupporting
confidence: 55%
“…We measured upper limb functional exercise capacity using the UULEX and found similar impairment as reported in people with COPD. 15,40 We observed that 85% of patients with ILD reported arm fatigue as the primary reason for ending the UULEX. In addition, we found a moderate association between elbow flexor muscle strength and the total exercise time.…”
Section: Discussionmentioning
confidence: 94%
“…UULEX is a test in which the exercise is increased to a maximum, which requires larger arm movements . In studies evaluating the concurrent validity of UULEX, the relationship with the 6PBRT has been found to be high, as both UULEX and the 6PBRT measure exercise capacity . The 30‐second push‐up test also evaluates the strength and endurance of the arm‐shoulder girdle and is a recommended test in the physical fitness test battery .…”
Section: Discussionmentioning
confidence: 99%
“…24 As soon as a participant finished each test, we recorded the band reached, total exercise time, self-reported dyspnoea and local muscle fatigue (using the MBS), and peak heart and …”
Section: 22mentioning
confidence: 99%